Optimalisasi Pengembangan Potensi Budaya Untuk Menunjang Keliki Cultural Park - Sutiarso, Moh Agus; Kuntariati, Utik; Pramana, I Gede Dimas Arya (Yayasan Kajian Riset dan Pengembangan RADISI, 2024)
The purpose of this community service activity is to improve the ability of human resources in managing the Keliki Cultural Park destination, as well as to preserve the culture of the Keliki village community amidst the rapid flow of modernization that has entered remote villages. Community Partnership Empowerment in Keliki village, Tegalalang, Gianyar is carried out through several stages, namely: Program Preparation and Socialization, Mentoring Activities, Monitoring and Evaluation, and Report Preparation. Mentoring activities related to the management of cultural-based tourism businesses in the Keliki tourist village are carried out by means of sharing sessions between the community service team and the management of the Tourism Awareness Group (Pokdarwis) as the manager of the Keliki tourist village. Quality cultural tourism management essentially requires a holistic, sustainable approach, and is centered on cultural preservation and local community participation. In this community service activity, assistance was also provided in the creation of culture-based tourism packages which are superior tourism packages sold to tourists. Promotion for marketing this tourism package uses the website and social media platforms Facebook and Instagram. The creation of culture-based tourism packages in Keliki village is an implementation of an approach that prioritizes cultural preservation, community involvement, and sustainability. The development of culture-based tourism in the Keliki tourist village can be a tool to strengthen local cultural identity while creating sustainable economic benefits for the local community.